2023
DOI: 10.1126/sciadv.ade9948
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided engineering of a receptor-agonist pair for inducible activation of the ABA adaptive response to drought

Abstract: Strategies to activate abscisic acid (ABA) receptors and boost ABA signaling by small molecules that act as ABA receptor agonists are promising biotechnological tools to enhance plant drought tolerance. Protein structures of crop ABA receptors might require modifications to improve recognition of chemical ligands, which in turn can be optimized by structural information. Through structure-based targeted design, we have combined chemical and genetic approaches to generate an ABA receptor agonist molecule (iSB09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…At present, multiple ABA analogs, such as AM1 [14], AMF4 [27], julolidine-and fluorine-containing ABA receptor activator (JFA1 and JFA2) [31], opabactin [18], and iSB09 [19], have a sulfonamide group, and their sulfonamide group resembles the carboxylate group of ABA. Combining yeast two-hybrid assays and PP2C inhibition experiments, it was found that SLG1 is mainly an agonist of PYL2 and PYL3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, multiple ABA analogs, such as AM1 [14], AMF4 [27], julolidine-and fluorine-containing ABA receptor activator (JFA1 and JFA2) [31], opabactin [18], and iSB09 [19], have a sulfonamide group, and their sulfonamide group resembles the carboxylate group of ABA. Combining yeast two-hybrid assays and PP2C inhibition experiments, it was found that SLG1 is mainly an agonist of PYL2 and PYL3.…”
Section: Discussionmentioning
confidence: 99%
“…Vaidya et al used virtual screening technologies combined with X-ray crystallography and structural designing to develop an amide compound opabactin, whose activity is ten-fold higher than ABA in both monocotyledonous and dicotyledonous plants from 18 million compounds [18]. Recently, through structural targeted design and structural modification, a sulfonamide sulfobactin (SB) derivative iSB09 was identified as an ABA agonist for the engineered CsPYL1 ABA receptor, named CsPYL15m CsPYL1 5m [19]. Therefore, the use of virtual screening technology to develop new ABA analogues is of great significance for improving the drought tolerance of crops.…”
Section: Introductionmentioning
confidence: 99%
“…The second category of ABA receptor selective agonists is characterized by a sulfonamide moiety serving as a linker arm. This group has garnered significant attention recently with examples such as pyrabactin, quinabctin, AMF4, cyanabactin, and the newly developed iSB-09 (Figure ). The crystal complexes of these sulfonamide ABA receptor agonists with PYLs show that their sulfonamide linker arm mimics the functional role of the carboxyl group in ABA. , Among these compounds, AMF4, derived from quinabctin, exhibits the highest potency and long-lasting effects in inducing drought tolerance in A.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic modification the coding genes of PYL/RCAR ABA receptors can improve plant water use efficiency in Arabidopsis , wheat, and maize, presenting a prospective target for engineering drought–tolerant crops under changing environmental conditions [ 10 , 11 , 12 ]. Moreover, chemical manipulation of ABA signaling by ABA agonists [ 13 , 14 ] and direct modification of PYL/RCAR ABA receptors by protein engineering [ 15 ] all have significant agricultural and ecological applications.…”
Section: Introductionmentioning
confidence: 99%